Impact of the FTO rs9939609 risk allele on subcutaneous adipose tissue fatty acid composition in adults with obesity class 2 and 3 - Ingrid Løvold Mostad; Valdemar Grill; Sissel Skarra; Ann Kristin Hjelle de Soysa; Barbara Fielding (PLoS ONE, 2026)
The FTO rs9939609 risk allele is linked to risk of obesity. Whether causality involves fatty acid (FA) metabolism remains to be fully investigated in adults with obesity. We tested for associations of the risk allele with the FA composition of android and gynoid subcutaneous adipose tissue. We recruited 95 participants with obesity class 2 and 3 and without diabetes, median BMI 42.8 (25 th , 75 th percentiles: 39.5, 46.5) kg/m 2 . Participants carried no (TT, n = 33), one (AT, n = 31), or two (AA, n = 31) copies of the FTO risk allele. Biopsies were obtained by aspiration and total FA composition determined by gas chromatography-mass spectrometry (GC-MS). In the cohort overall, there were no significant genotype associations with any single FA. In males with the TT allele, mass of oleic acid (18:1n-9) in the gynoid depot was higher compared with the AT allele when corrected for depot size. We interpret these findings with caution due to the small numbers of males with the TT genotype. Disregarding genotype, in the cohort overall, proportions of saturated FAs were higher, and proportions of monounsaturated FAs lower in android versus gynoid adipose tissue, confirming previous studies. We found previously unreported sex-related differences in FA composition (weight %) and content (weight % corrected for depot mass). Our findings on FTO genotype are generally negative; observations to the contrary require confirmation as does the non-genetic and novel results on sex-related differences.